The Influence Of Online Customer Reviews And Brand Trust On Purchasing Decisions For Egtn Somnium Products On The Shopee Marketplace Application (Survey Of Egtn Somnium Hoodie Consumers In Tasikmalaya) : - Indriyani, Silfia; Arisman, H Ari; Arif, Arif (CV. Utami, 2024)
This research aims to determine and analyze the influence of online customer reviews and brand trust on purchasing decisions for Egtn Somnium hoodie products on the Shopee marketplace. The method used in this research is causality through a survey approach, with a research sample of 100 Egtn Somnium hoodie consumers in Tasikmalaya. The data used uses primary data. The analytical tool used is multiple linear regression using SPSS 25 software. The research results show that online customer reviews and brand trust simultaneously have a significant influence on purchasing decisions for egtn somnium hoodie products on the shopee marketplace. Online Customer Review partially has a significant influence on purchasing decisions for Egtn Somnium Hoodie products at the Shopee Marketplace in Tasikmalaya. Brand Trust partially has a significant influence on purchasing decisions for Egtn Somnium Hoodie products at the Shopee Marketplace in Tasikmalaya.